A component build-up approach for aerodynamic prediction of a winged ducted-propeller micro air vehicle. (6th January 2011) - Tobing, Sheila; Go, Tiauw Hiong
Characterised by low aspect ratio lifting/control surfaces and flight in the low Reynolds number regime, a typical micro air vehicle (MAV) generates complex flow phenomena that cannot be accurately predicted using conventional-aircraft design tools. This flow complexity motivates the use of advanced computational fluid dynamics (CFD) tools even in the conceptual design stage. However, the use of full CFD simulations during the conceptual design stage is not realistic due to time and computational cost constraints. This paper proposes an innovative solution based on the component build-up method (CBM), which is consistently used in conventional-aircraft design to predict the full vehicle aerodynamic performances. In order to take into account, the complex phenomena of aerodynamic interferences and mutual flow perturbations generated by the lifting surfaces while still maintaining a low computational cost, an improved CBM approach was proposed to allow quick prediction of aerodynamic coefficients of a winged ducted-propeller MAV at various configurations. Comparisons of results between this efficient method and CFD are also presented to validate the approach.